(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Abdulla Bobokhanov, also known as Bobokhanov Abdulla Bobokhanovich, is a significant figure in the architecture of Uzbekistan. His work and influence are critical in shaping modern Uzbek architecture while integrating traditional elements. Here are some key aspects of his contributions.